Dampak Pemberdayaan Perempuan terhadap Perilaku Ekonomi Rumah Tangga (Studi Kasus pada Kelompok Wanita Tani di Kota Prabumulih, Sumatera Selatan) - Rona Anggrainie; Siska Alfiati (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Anggrainie R, Alfiati S. 2019. The impact of women’s empowerment on household economic behavior (case study of farmer women’s group in Prabumulih, South Sumatra). Jurnal Lahan Suboptimal: Journal of Suboptimal Lands. 8(2):192-201. This study aimed to analyze the level of family welfare as a result of the empowerment of women through the Women Farmers Group. The analytical method was carried out descriptively by tabulating data, then analyzed by comparing with the reference level of the prosperous family and its indicators based on the conditions set by the BKKBN. To analyze the impact of women's empowerment on household economic behavior, it was carried out using multiple linear regression analysis. Sampling was carried out by a simple random sampling method of 60 housewives who were members of the Wanita Tani Group. The results of this study indicated that when viewed from the indicators set by the BKKBN, the majority of Women Farmers Households were in the Prosperous Family II category. Simultaneously, the variable intensity of the participants, the number of family members, the age of the mother, the level of education of the mother had a significant effect on the level of income, maternal work time, and household consumption in the City of Prabumulih. But partially, the intensity of the participants had a significant effect on time spent working and household expenses, while on household income was not significant.